Hypothetical cosmogonic conception of the World order in the Tagar culture - Polyakova, O.O. (Archaeoastronomy and Ancient Technologies, 2014)
The article analyses two works by V.E. Larichev, where he reveals a potential occult astral aspect of the petroglyphs dating back to the Tagar culture of the late I millennium BCE in Northern Khakassia, namely, in the foothills of the Kuznetsk Alatau at the southern submontane extremity of Chetvyorty Sunduk. Professor Larichev’s astral compositions provide the opportunity for further archaeo-astronomical research. The characters of the pictorial petroglyphic compositions represent ancient cosmic symbols of not only the Tagar culture, but also of many Eurasian peoples’ cultures. This is the cosmic unity which joined minds of ancient representatives of various Eurasian cultures and generated in each of them the idea of a Heroic epos, Heroes bearing different names, but the plotline being actually the same, including fighting, development and defeating similar enemies. The plot is the same and it was suggested by the circumpolar pattern of the northern stellar sky, similar for all the inhabitants of the northern hemisphere of the Earth at the same Age. The petroglyphs of Chetvyorty Sunduk prove ancient people’s knowledge of such phenomena as the precession, the motion of the celestial pole among stars and the location of the pole of the ecliptic near Draco’s «head».